Untangling Dynamic and Operational Capabilities: Strategy for the (N)ever‐Changing World - Helfat, Constance E.; Winter, Sidney G. (Strategic Management Journal, 2011)
Abstract We explain why the line between dynamic and operational (or ordinary) capabilities is unavoidably blurry, draw implications for capabilities that promote economically important but seemingly gradual change, and provide recommendations for future research that takes these issues into account. Copyright © 2011 John Wiley & Sons, Ltd.